Mama : a novel - McMillan, Terry (New York : Pocket Star Books, 1987)
Mildred Peacock, a spirited African-American woman living in the declining Michigan town of Point Haven, decides to kick out her jealous husband, Crook, and raise her five children on her own.
Keywords: AFRICAN -- AMERICAN -- WOMEN